Respon Pertumbuhan Tanaman Kacang Panjang Ungu (Vigna Sesquipedalis L. Fruwirth) Terhadap Pupuk Organik Cair Air Cucian Beras dan Cangkang Telur serta Interval Waktu Pemberian - didan faik fuadi; Siti Asmaniyah Mardiyani; Abdul Basit (AGRONISMA, 2022)
Purple long bean (Vigna sesquipedalis L. Fruwith) is a commodity that has a purple color in its fruit which contains high anthocyanins and is useful as an antioxidant. This study was to determine the effect of concentration and time interval of giving liquid organic fertilizer, rice washing water and egg shells on the growth of purple long bean plants. This research was conducted in February in Kemuning Hamlet. The study used a factorial RAK with a control consisting of 2 factors. Factor 1 concentration of POC consists of 3 levels, namely P1= 50ml L-1, P2= 100ml L-1 and P3= 150ml L-1. Factor 2 the time interval of administration consisted of 3 levels, namely W1= once every 3 days, W2= once every 5 days and W3= 7 days so that 10 treatments including control were obtained, each treatment was repeated 3 times, 30 treatment units were obtained, each treatment consisted of 4 samples so that 120 units of plant samples were obtained. The results showed that P2W2 treatment (concentration 100ml L-1 at intervals of 5 days) gave the best interaction effect on plant length variables at the age of 14 days after planting, 87.39cm, 21 days after planting, 136.16cm, and 28 days after planting 216.58cm, the number of leaves was 21 days after planting, 31 days after planting. 00 pieces and 28 days after planting 54.16 leaves, leaf area 14 days after planting 585.00cm2 and 28 days after planting 1412.15cm2, leaf chlorophyll content 20 days after planting 44.16 Âµg/ Â and 30 hst 40.60 Âµg/ . The P3W2 treatment (concentration 150ml L-1 at intervals of 5 days) gave a good interaction effect on the variables of root length 22.04cm and number of flowers 11.94 cm.Key words : Long bean plant, POC concentration, time interval of administration, egg shells, rice washing water